دراسة مقارنة لثلاث طرق لمعالجة شلل بل - محمود عزيز; يوسف يوسف; سليمان فراس (Latakia University Journal -Medical Sciences Series, 2019)
شلل بل عند الأطفال والبالغين سبب شائع لاستشارة اختصاصي أمراض الأذن والأنف والحنجرة وهو يمثل مشكلة تشخيصية وعلاجية معقدة. والهدف من البحث هو تحديد جدوى كل من الطرق العلاجية الثلاث المتبعة في هذا البحث من خلال دراسات سريرية وفحوص متممة. تناولت الدراسة (90) شخصاً لديهم شلل بل, قسموا لثلاث مجموعات متساوية, مجموعة أولى عولجت بالبردنيزولون, ومجموعة ثانية عولجت بالديكساميتازون بجرعات عالية, ومجموعة ثالثة عولجت البردنيزولون مع الاسيكلوفير. وقد تبين أن المعالجة بالبردنيزولون هي الطريقة الأفضل في المعالجة. Bells` palsy is a common cause for consultation of a specialist of ENT; it represents a complicated diagnostic and therapeutic problem. The objective of the study is to know the feasibility of everyone of the three methods by clinical studies and completed tests. The study involved (90) persons who suffered from Bells` palsy. They were divided into 3 groups: the first was treated with prednisolone; the second with high doses of Dexamethasone; and the third with prednisolone and acyclovir. The result was that prednisolone therapy was the best method of treatment.